The concomitant crystallization of two polymorphs of 1-deoxy-alpha-D-tagatose. - Jones, N; Jenkinson, S; Soengas, R; Izumori, K; Fleet, G; Watkin, D (2007)
The crystalline form of 1-deoxy-D-tagatose, C6H12O5, is shown to be 1-deoxy-alpha-D-tagatopyranose; the absolute configuration is determined by use of D-lyxono-1,4-lactone as the starting material. The title compound crystallized as concomitant polymorphs from a mixture of ethyl actate and methanol. Although the melting points of the materials differ by 7 K, the molecular conformations are almost identical and, in both polymorphs, each molecule is subject to four O-H...O hydrogen bonds.